Church-Related Hospitals and Health-Care Provision in Zimbabwe - Sophia Chirongoma (Palgrave Macmillan, Cham, 2022)
This chapter analyses the role of the Zimbabwe Church Health Association (ZACH). The author discusses the role of the missionaries in the provision of health care in the country. Further, she analyses the partnership between church hospitals and the government after independence. She maintains that during the crisis years church hospitals continued to operate when government hospitals ground to a halt. The chapter underscores the role of the churches in contributing to health in Zimbabwe.